Kerala's turnaround in growth: role of social development, remittances and reform - Kannan, K.P. (2005)
Kerala, which has been known for its high human development but low economic growth, is now exhibiting a new phenomenon. Growth has accelerated since the late 1980s, as a result of economic reforms and a large inflow of remittances. However, the challenge remains of translating its high human development status and relatively rapid growth into meaningful outcomes in employment and equitable participation of women. - Reproduced.
Keywords: Economic reform - India - Kerala; Economic and social development - India - Kerala; Economic growth - India - Kerala; Economic growth